Adsorptive recovery of ethylene by CuCl2 loaded activated carbon via π-complexation. Issue 6 (July 2016) - Zhou, Xiaolong; Feng, Minchao; Niu, Hui; Song, Yueqin; Li, Chenglie; Zhong, Dongwen
Ethylene is recovered from ethylene/ethane mixture by adsorptive separation on CuCl2 loaded activated carbon. When 36.7% of CuCl2 were dispersed on activated carbon made from coconut shell (CSC) and calcined at 400℃ for some hours, a satisfactory adsorbent sample was prepared. The adsorption capacity of ethylene reached 23.55 mg/g and ethylene/ethane separation factor reached 7.6. Adsorbent characterization by various modern instruments demonstrated the reduction of CuCl2 to provide Cu + cation on CSC, which is responsible to form π-complexation bonds for the adsorption of ethylene. Mechanism was discussed. Nature of related active centers was suggested.